Study on Vibration Suppression of Bevel Gear with Integral Squeeze Film Damper - Liang Ma; Lidong He; Kaihua Lu; Yipeng Zhang; Zhao Chen (Jixie chuandong)
Aiming at the problem of vibration reduction and noise reduction of bevel gear transmission system，a method for solving the vibration of bevel gear by using an integral squeeze film damper（ISFD） is proposed. An experiment bench of bevel gear transmission system is built，and a comparative study is conducted on the vibration characteristics of the bevel gear transmission system with rigid support and ISFD elastic damping support. The experimental results show that the ISFD elastic damping support can reduce vibration significantly in a wide frequency range with excellent damping performance，and the reduction of vibration acceleration of the bearing block is up to 40%. Comparing the vibrations of bevel gear transmission system at different speeds，it is verified that the ISFD elastic damping support has a great effect on vibration reduction over a wide speed range.